Reconstruction of Moderation Values in the Exemplary Method in Da’wah - Anrial, Anrial; Junaidi, Heri (Institut Agama Islam Negeri (IAIN) Curup, 2023)
This article explores reconstructing the values of moderation of da'wah messages towards Islam rahmatan lil 'alamin. The purpose of this writing is to look at the da'wah messages conveyed at this time which are sometimes out of the context of unity and have a lot to do with new doctrines that leads to intolerance, both towards culture and towards adherents of other religions, so it is necessary to provide guidance at this time for preaching messages so that social problems do not occur in society. The method used in this research is a qualitative method which is a literature study. The data sources in this research are journals, books, opinions and news related to this research. From the results obtained, the appropriate form of da'wah in reconstructing the values of moderation is da'wah by example. This can be seen from the exemplary da'wah of the Prophet Muhammad to people who had different cultural and religious backgrounds at that time, so that the form of da'wah was exemplary. is one of the most appropriate ways for preachers to instill the value of moderation in society.